METHODS FOR USING CHILDREN'S FOLK GAMES TO TEACH NUMBERS AND COUNTING IN PRIMARY EDUCATION - G.K.Raximova, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article talks about the methods used in teaching numbers and numbers to elementary school students, and the importance of folklore examples